Turbulensi Ekonomi Global Akibat Pandemi Covid 19 dan Dampaknya Pada Kota Bekasi - Hasanuddin; Djuni Thamrin; Cahyadi Husadha; Tutiek Yoganingsih (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
This study was conducted to determine the pressure experienced by the Bekasi City Government during the Covid 19 period, by comparing regional revenue and expenditure budget data from 2016 to 2021 from the budget side, especially on the side of regional income, regional expenditure, and regional original income. This study uses qualitative methods and the source of data used in this study is secondary data. This study found that the pre-Covid-19 budget posture, especially in 2016 and 2018 Bekasi City's income increased even though there was still a deficit because regional spending was still greater than regional income. Strong pressure on the Bekasi City budget occurred at the end of the 2019 fiscal year. The 2020 budget for all sources of Bekasi City income fell, this explains that the Covid 19 Pandemic is a determining factor in the shocks experienced by Bekasi City. The same thing happened in the 2021 Budget, sources of income such as regional taxes and regional levies still could not reach the target.